EFFECT OF TREATMENT TEMPERATURE ON STRUCTURE FORMATION IN CR-MO-V STEEL (Modern Problems of Metallurgy, 2024)
Properly selected heat treatment, which have the purpose to create a structure that would satisfy the requirements of the manufacturer, is the main way to improve the quality characteristics of the steel. The investigated steel 31CrMoV9 was heated to temperatures in the range of 850-1050°C and cooled in water and air. The structure consisted of bainite and martensite with different ratios, after normalization. An increase in the heating temperature leads to an increase in the amount of martensite from 5-10% at 850°C to 50% at 1050°C, that was shown by investigation. The microhardness of the steel increases respectively. The structure of the 31CrMoV9 steel consists of the tempered martensite, which is characterized by various morphology, after heating to different temperatures, quenching and tempering. Average of the microhardness of the steel decreases with an increase in quenching temperature. The change of the microhardness is probably due to an increase in the volume of residual austenite and the dissolution of alloyed carbides. Detected that with an increase in the heating temperature, an increase in the initial austenite grain led to the enlargement of martensite needle. Determined, that with increasing heating temperature, the dispersion of pearlite depends on the size of austenitic grains. An increase in the austenization temperature leads to an increase in the interplate distance. The alloy steel should be heated at the temperature of 850°C to obtain the uniform structure.